The Phenomenon of Women Entrepreneurship and its Contribution to the Supply Chain Promotion: A case of Indonesian Supply Chain Companies - Muchran, Muchran; Badruddin, Syamsiah; Idrus, Arifin; Halim, Paisal (International Journal of Supply Chain Management, 2020)
Objective of this study is to examine the role of women entrepreneurship practices in supply chain promotion. For this purpose, Indonesian supply chain companies were selected. It was observed that Indonesian supply chain companies are suffering due to ineffective supply chain activities. Due to supply chain issues, the performance of these companies is declining. Most of the previous studies highlighted supply chain among various organizations, however; literature ignore the role of women entrepreneurship practices to promote supply chain. For this purpose, data were collected from the employees of supply chain companies with the help of questionnaire survey. Data were analyzed with the help of Partial Least Square (PLS). Results of the study highlighted that women entrepreneurship practices have significant role to enhance supply chain practices among Indonesian supply chain companies. Moreover, women previous entrepreneurial experience and entrepreneurial passion for inventing has positive on supply chain promotion. Thus, this study has significant importance for Indonesian supply chain companies.